Microplastics in the Bay of Biscay: An overview. (April 2020) - Mendoza, Amaia; Osa, Juan Luis; Basurko, Oihane C.; Rubio, Anna; Santos, María; Gago, Jesús; Galgani, François; Peña-Rodriguez, Cristina
Abstract: Microplastics (MPs) are an environmental problem of growing concern, and several studies have defined the Bay of Biscay (BoB) as a marine litter accumulation area. To address the abundance of MPs in this region, a critical overview is presented compiling the research performed to date on the different water bodies, sediments and biota. The comparative assessment highlights high spatial and temporal variability in MP distribution. MPs appear in at least 50% of the samples in waters and sediments. Polypropylene, polyethylene, polyester and polystyrene are the most frequent polymers, with a significant predominance of fragments and fibres. The BoB can be considered a region with medium concentration of MPs. However, monitoring programmes are needed to compile data over time and thus evaluate the historical trends of MP pollution. The difficulty of comparing studies is highlighted, due to the use of different methodologies. Hence, the harmonisation of monitoring methods is urgently required. Highlights: The Bay of Biscay presents a medium level of MP pollution. A high spatial and temporal variability is found in each marine compartment. Polypropylene, polyethylene, polyester and polystyrene are most frequent MPs. Harmonisation of methods to study the abundance of MPs is needed.